Endodontic Management of Permanent Mandibular Teeth having Rare Morphological Variations in Root Canal Anatomy—A Case Report - Monica Yadav; Supriya S. Ojha; Shweta Raj; Gaurav Jain; Preeti Shukla; Pradyumna Misra (Journal of Pharmacy and Bioallied Sciences)
By completing an optimal root canal treatment, endodontic therapy aims to repair the damaged periapical area by removing microorganisms and their by-products from the infected root canal space. Nonetheless, a number of variables, such as understanding the architecture of root canals, precise diagnosis and treatment planning, and subsequent management of any anatomical variation in the affected tooth, all have a significant impact on the outcome of an endodontic procedure. There may always be differences, even though research indicates that most permanent human dentition has a similar root canal architecture. Therefore, it is critical to detect these morphological changes since failing to do so might have unfavorable effects and affect how well the medication is administered. Ignorance of anatomical variance, leading to a missing canal, is one of the most frequent causes of endodontic failure. In this case study, uncommon clinical symptoms in mandibular teeth—which are typically single-rooted—are discussed along with the endodontic treatment that followed.